Semiárido de possibilidades: reestruturação produtiva e dinâmica territorial no Distrito de Ribeira, Cabaceiras (PB) - Medeiros, Verônica Pereira de (2018)
The semiarid as a changing territory presents new complexities. In light of this, we make an effort to reflect on the constructed imaginary, the paradigmatic change generated by the various ways of thinking and acting in that territory and show the context of new looks and possibilities, and also think about the process of productive restructuring and the role of the new subjects, in other words, organized civil society. Given the different uses of the semiarid territory, we consider that it’s possible to talk about the existence of “semiarids”, since there are, in the current environment, other elements that must be considered, such as the presence of significant changes in the political and economic scenario. That said, the main objective of the research is to understand the process of productive restructuring of the District of Ribeira, in the municipality of Cabaceiras (PB), taking into consideration the consequences of this process in the current territorial dynamics. Regarding the research procedures, these focused on the following: bibliographic survey, search of secondary data and fieldwork. Added to these procedures are interviews and dialogues with important social subjects to bring our study closer to the reality. The information obtained shows that the process of changes in the analyzed territory was intensified by the modernization of two economic activities: garlic and leather goods production, the main responsible for income generation in the District. As a result of our interpretation, we learn that the changes in the productive base, that is, horticulture and leather craft production, made possible economic changes that materialize in space, due to the increase in income and public and private investment, and promoted the visibility of the District making it an attractive territory for the media and for those who visit the region. From the political point of view, we observe the increase in the levels of political representation due to the election of politicians who have established relations of belonging with Ribeira and from the socioeconomic one, the value added in the products offered by the Leather Workers Cooperative of Ribeira in Cabaceiras (ARTEZA), in addition to the revaluation of the leather activity associated with the differentiation of skins quality with the vegetable tanning and the competitive advantages for more demanding markets. These elements are enabing the increase of income and the improvement of the living conditions of the population and contributes to consolidate our reading of the semiarid as a territory of possibilities.